Evaluation of Arsenic-Induced Stress in Dahlia pinnata Cav.: Morphological and Physiological Response. Issue 7 (3rd October 2019) - Raza, Ali; Khan, Aqib Hassan Ali; Nawaz, Ismat; Qu, Zhiguo; Yousaf, Sohail; Ali, Muhammad Arif; Sayal, Aziz Ullah; Iqbal, Mazhar
ABSTRACT: Arsenic (As) is a carcinogenic metalloid that poses serious health and environmental threats to human. We explored the potential of Dahlia pinnata Cav., which is a known ornamental plant, for phytoremediation of As. Impacts of increasing As concentrations (0–120 µM) on growth and biochemical parameters of D. pinnata were evaluated. At lower As stress (5 µM—a concentration which is toxic for many plants species), growth performance of D. pinnata remained stable, whereas higher As concentration lead to an obvious deleterious effect, with no growth after 4 weeks of As exposure (at concentration higher than 80 µM As). Roots were found to accumulate high levels of As. Chlorophyll a, b and carotenoids contents were enhanced at low concentration and at higher As concentration significant decrease was observed. Activities of antioxidant enzymes like catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), guaiacol peroxidase (GPX), and glutathione S-transferase (GST) were found to be affected variably by As exposure, in D. pinnata . In conclusion, D. pinnata is a nonaccumulator however, the As tolerance limit (5 µM = 370 µg L −1 ), growth performance and tendency of the plant to keep most of absorbed As in its root make it a potential candidate for the phytostabilization purposes of As-contaminated sites.